Economic literacy program on entrepreneurship behaviors in quechua speakers rural landscapes residents, Caraz - Paredes Tarazona, Mildred (2014)
The effectiveness of economic literacy program in the development of entrepreneurial behaviors in Quechua speaking people Caraz, Ancash was studied. Economic literacy conceived as a valid strategy in the intergenerational transmission of knowledge to the formation of basic economics applied to the management of production units. A quasi-experimental pre and post-test, and qualitative around collective imaginary design was used. Economic Literacy Program, independent variable, and entrepreneurial behavior, dependent variable; observed in the sample of the experimental group consisting of rural landscape residents collaborators Queral and control group, parents of 3rd grade of IE 2 de Mayo, Caraz. Was applied: Questionnaire knowledge of knowledge, Behavior Observation Record Entrepreneurship (ROCE-2010) and the Scale of Attitudes Toward Entrepreneurship (EAE-2010 Reliability 0.83). Descriptive statistical and inferential the nonparametric data were analyzed. It was found that the Program of Economic Literacy affects behaviors Entrepreneurship, also expressed in the formation of a productive unit that had a commercialized and reinvested a product of their cultural expression (UNESCO, 2005) production.